High-fidelity VLA imaging of the radio structure of 3C 273 - Perley, R. A.; Meisenheimer, K. (Astronomy and astrophysics (Berlin), 2017)
Context. 3C 273, the nearest bright quasar, comprises a strong nuclear core and a bright, one-sided jet extending ~23 arcsec to the SW. The source has been the subject of imaging campaigns in all wavebands. Extensive observations of this source have been made with the Very Large Array and other telescopes as part of a campaign to understand the jet emission mechanisms. Partial results from the VLA radio campaign have been published, but to date, the complete set of VLA imaging results has not been made available. Aims. We have utilized the VLA to determine the radio structure of 3C 273 in Stokes I, Q, and U, over the widest possible frequency and resolution range. Methods. The VLA observed the source in all four of its configurations, and with all eight of its frequency bands, spanning 73.8 MHz to 43 GHz. The data were taken in a pseudo-spectral line mode to minimize the VLA’s correlator errors, and were fully calibrated with subsequent self-calibration techniques to maximise image fidelity. Results. Images in Stokes parameters I, Q, and U, spanning a resolution range from 6 arcsec to 88 milliarcsec are presented. Spectral index images, showing the evolution of the jet component are shown. Polarimetry demonstrates the direction of the magnetic fields responsible for the emission, and rotation measure maps show the RM to be very small with no discernible trend along or across the jet. This paper presents a small subset of these images to demonstrate the major characteristics of the source emission. A library of 294 images has been made available at the CDS.